(untitled) (Baghdad Science Journal, 2024)
The research interest in nanomaterials preparation from natural products as a green method and their application in various fields applications, tremendous attention has been taken to the green composition of nanoparticles. ZnO can be considered one of the most widely used metal oxides for most requirements of daily used products. In this research ZnO NPs prepared by using Petroselinum crispum (parsley) extract and to make the first study of toxicological evaluation of ZnO NPs their effect aspects on Honey bees (Apis mellifera). ZnO NPs have been charactarized by using SEM, EDX, XRD, UV-Vis and FTIR Spectroscopy. The toxicological evaluation of ZnO NPs has been applied to a honey bee. The lethal ZnO concentration was obtained, and the LC50 range calculation values ​​were changed during 288 hours of feeding to ZnO nanoparticles at different concentrations (25, 50, 250, 500 mg per 100 ml) and the obtained LC50 values changed from 275, decreasing to 162.55 for the research range times after every 24 hours of exposure feeding calculations. In addition, for the group treated with 500 mg of ZnO per 100 ml, higher mortality was observed compared to other concentrations as it increased more than all other items indicating the above concentrations but not with the control group. The ergonomic design for creating a honey bee shelter was first introduced and no similar investigations were found in the literature.